Loaf Characteristics and Sensory Properties of whole Wheat Bread Fortified with Sorghum and Rice Flour - Iftikhar Ahmed Solangi; Nida Shaikh; Asadullah Marri; Aijaz Hussain Soomro; Shahzor Gul Khaskheli (Journal of Basic & Applied Sciences, 2017)
Bread is a common staple food in developing countries and also in many other regions of the world. The loaf characteristic and sensory attributes of bread samples prepared by using different composite flours in which ratio of whole wheat flour, sorghum flour and rice flour kept as 100:0:0 (F1), 80:10:10 (F2) and 60:20:20 (F3) was evaluated. The composite flours F1, F2 and F3 were subsequently used for making bread samples i.e. whole wheat bread (WWB), sorghum rice bread-1 (SRB-1) and sorghum rice bread-2 (SRB-2), respectively. The results indicated that significantly higher loaf weight (g) was recorded in SRB-2 followed by SRB-1 and WWB. Significantly higher bread height (cm) was noticed in SRB-1 followed by WWB and SRB-2. The bread sample WWB was found to have significantly higher volume and specific volume followed by SRB-1 and SRB-2. It was also revealed that significantly higher average score for bread crust color was perceived by WWB. However, bread sample SRB-1 perceived significantly higher score (P<0.05) for crumb color, texture, aroma, taste and overall acceptability. It is concluded from present study that fortification of bread with different proportions of rice and sorghum flour was found to improve sensory attributes of the bread samples rather than loaf characteristics.